A global scientific strategy to cure hepatitis B. (July 2019) - ,; ,; ,; Arbuthnot, Patrick; Boonstra, Andre; Chang, Kyong-Mi; Chen, Per-Jei; Glebe, Dieter; Guidotti, Luca G.; Fellay, Jacques; Ferrari, Carlo; Jansen, Louis; et al.
Summary: Chronic hepatitis B virus (HBV) infection is a global public health challenge on the same scale as tuberculosis, HIV, and malaria. The International Coalition to Eliminate HBV (ICE-HBV) is a coalition of experts dedicated to accelerating the discovery of a cure for chronic hepatitis B. Following extensive consultation with more than 50 scientists from across the globe, as well as key stakeholders including people affected by HBV, we have identified gaps in our current knowledge and new strategies and tools that are required to achieve HBV cure. We believe that research must focus on the discovery of interventional strategies that will permanently reduce the number of productively infected cells or permanently silence the covalently closed circular DNA in those cells, and that will stimulate HBV-specific host immune responses which mimic spontaneous resolution of HBV infection. There is also a pressing need for the establishment of repositories of standardised HBV reagents and protocols that can be accessed by all HBV researchers throughout the world. The HBV cure research agenda outlined in this position paper will contribute markedly to the goal of eliminating HBV infection worldwide.